Penggunaan Media Diorama dan Hasil Belajar Siswa Materi Lingkungan Pada Kelas I SD Negeri 16 Sungailiat - Astinah, Astinah; Suryadin, Asyraf; Wahyuningsih, Eka (Yayasan Pondok Pesantren Sunan Bonang Tuban, 2023)
This research was motivated by some students who are in asking or answering questions during the learning process. I learning media that are around the school environment such as plants, sand, and stones so that in learning students were less focused and quickly feel bored. This study aimed to determine the effect of the use of diorama media on the activeness of student learning environment material in first-grade of SD Negeri 16 Sungailiat. The approach used in this research is quasi-experimental quantitative using nonequivalent control group design. The instruments used are questionnaires and multiple choice test. This research was contucted at SD negeri 16 Sungailiat. The sample technique used was saturated sampling in class 1 totaling 52 students. The results showed that, from testing the hypothesis using an independent test sample test showed that the results of the hypothesis obtained from the value of ? count was 6.103 and ? table was 2.009, then ? count > ? table was 6.103 > 2.009 and contained in Sig. (2-tailed), namely the pretest and posttest have a value of 0.000 < 0.05.